HUBUNGAN TINGKAT EMOSIONAL DENGAN PERILAKU PENGEMUDI DALAM BERLALU LINTAS - Hardiansyah Hardiansyah (Inersia: Jurnal Teknik Sipil, 2018)
Traffic accidents caused by several factors, among others, are human beings, vehicles, roads and environment, of the four human factor plays a very dominant because a lot of factors that influence behavior. Using methods of questionnaire with 15 scenarios that show the behavior of respondents when driving a motor vehicle or in everyday life is accompanied by expressions of anger in the form of anger that was issued (O), moved (D) and silent (S), with the number of respondents as many as 60 people consisted of 31 male respondents - 29 male and female respondents. From the results of the analysis and discussion shows the following behavior: Based on the age level of anger at the attitude of the respondents considered somewhat angry and upset. Based on the old SIM ownership on the attitudes of respondents angry categorized. Based on bit longer driving experience on the attitudes of respondents considered a little angry. Based on a day long trip on the attitudes of respondents categorized little angry, but for the respondents who traveled per day more than 86 km are categorized on the attitude a little angry. Based on respondents' gender attitudes are categorized on a little angry. Anger is the respondents who expressed no anger issued (O), but expressed anger that moved (D) and silent (S).